2022
DOI: 10.1186/s41182-022-00422-7
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid antiviral efficacy against SARS-CoV-2 omicron variant in vitro

Abstract: The coronavirus disease 2019 (COVID 19) pandemic continues to pose a threat to global health. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant (B.1.1.529) has spread rapidly worldwide and became dominant in many countries. A natural 5-aminolevulinic acid (5-ALA) with sodium ferrous citrate (SFC) has demonstrated antiviral activity in Wuhan, Alpha, Beta, Gamma, and Delta variants of SARS-CoV-2 infections in vitro. In this study, we report antiviral activity of 5-ALA, 5-ALA with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The infected cell supernatant was quantified using qRT‐PCR described in previous reports [51,52] . To confirm our quantitative assay, the previously reported anti‐viral effects of remdesivir and virus‐containing medium were used as positive and negative controls (virus only), respectively [53–55] . The experiments were conducted in duplicate to determine the IC 50 .…”
Section: Methodsmentioning
confidence: 99%
“…The infected cell supernatant was quantified using qRT‐PCR described in previous reports [51,52] . To confirm our quantitative assay, the previously reported anti‐viral effects of remdesivir and virus‐containing medium were used as positive and negative controls (virus only), respectively [53–55] . The experiments were conducted in duplicate to determine the IC 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in vitro experiments with different SARS-CoV-2 strains showed that even low concentrations of 5-ALA with SFC inhibited replication of the Wuhan, alpha, and delta strains. Higher concentrations were effective against the beta and gamma strains[41].…”
mentioning
confidence: 95%